A multi proxy investigation into the effects of burial environments on nuclear DNA in bone over forensic and archaeological timescales - Harrison, Deborah L. (Cranfield University, 2016)
This research conducted a two-pronged approach to study the effects of taphonomic processes by conducting analysis of experimental burials of porcine femora and parallel analysis of ancient human archaeological remains from geologically distinct cemeteries. The aim of this study was to identify the major degradative factors from depositional environments that affect the bone composition and the retention and retrieval of nucleic DNA from archaeological bone. Four different experimental burial environments of clay, compost, lime and sand were designed, displaying different properties of soil type, pH, water content and organic content. Analysis of the burial mediums and bones were conducted at regular intervals over an 18 month period. Observations of changes in the burial medium, comparisons of the rates and degree of soft tissue decomposition, bone diagenesis from compositional assessment, and bone colour change were made and analysed in correspondence with the different environments. The analytical data collected on the diagenesis of the archaeological bone from both studies, was compared to the DNA profiling success rates. The research and optimisation of sample preparation and DNA analysis enabled the most cost-effective and appropriate methods to be identified and utilised in accordance with the preservation state of the bone samples. This allowed the analysis of ancient archaeological bone to be analysed in-line with forensic protocols, to enable a uniform accessible approach to produce comparable results across different laboratories. Drawing together the results from the various analytical techniques made it possible to identify the variables that affect bone diagenesis and the survival of nuclear DNA, and provide evidence that the rate of decomposition and bone degradation is affected more significantly by the burial environment than duration of burial, as stated in the research hypothesis. The presence of water, sand and the level of organic content were found to be the most degradative variables within the experimental burial conditions; causing changes in bone crystallinity, and infiltration of contaminants into the bone. The presence of lime, chalk or limestone in an environment was found to have preserving properties in both the porcine and human burials, by retarding the rate and degree of soft tissue decomposition, and reducing the diagenetic changes in bone composition evident from the other environments. Despite previous reports of success using analytical techniques as predictive models for DNA and bone preservation, no correlations with DNA survival could be established. However the use of a multi-disciplinary approach enabled the detection and identification of soil contaminants affecting the bone structure and the ability to amplify DNA, in relation to burial environments. This research highlighted the importance of utilising multiple analytical techniques, such as colourimetry, ATR-FTIR, XRF and genetic analysis in order to avoid misinterpretation and false reporting of the state of bone diagenesis or preservation and the survival of DNA, due to environmental contaminants within the hard tissue. The research confirms the idea that in order to establish optimised sampling and DNA analysis of archaeological bone, it is imperative that certain protocols are adhered to. Precautions must be implemented from excavation through to laboratory analysis to avoid contamination; and correct recording of burial environment is essential to enable consideration of extrinsic factors and contaminants when reporting results.